ANALYSIS OF THE EFFECTIVENESS OF CIVIC EDUCATION LEARNING BY USING THE WHATSAPP OF STUDENTS ON SMAN 1 KUOK KAMPAR, 2021-2020 - Rifka Rahma Yani; Gimin; Supentri (JURNAL RANDAI, 2021)
The distance education system is one of the solutions to overcome difficulties in face-to-face learning. WhatsApp is a social media that is used as a means of sending educational stimuli virtually (Learning Platform). This research was conducted to determine the effectiveness of Civics learning using WhatsApp. The formulation of the research problem is "How is the effectiveness of Civics learning using WhatsApp and what is the frequency or level of provision for using WhatsApp in Civics learning for students of SMAN 1 Kuok, Kampar Regency, 2020-2021 academic year?" This study aims to analyze the effectiveness of Civics learning and identify the frequency or level of provision for using WhatsApp using WhatsApp. This research was conducted in August-October 2020. The research sample was 101 students of SMAN 1 Kuok, the sampling technique was purposive sampling using sample development from Isac and Michael with a significance level of 10%. Researchers used documentation of student learning outcomes, questionnaires, and literature study to collect data. Researchers used quantitative descriptive methods to analyze the data that had been collected. The results of this study indicate that Civics learning using WhatsApp is categorized as Less Effective as indicated by the N-Gain Score of student learning outcomes, the N-gain percentage is 54.76% and the total questionnaire score is 4,808 (54.10%) of the score expected to be 8,888 (100%)